OP0075 A 6-Month, Phase 2, Open–Label, Single-Arm Study to Evaluate the Safety and Efficacy of Treatment with Canakinumab of Pediatric Patients with Colchicine Resistant Familial Mediterranean Fever. (23rd January 2014) - Brik, R.; Butbul Aviel, Y.; Lubin, S.; Ben Dayan, E.; Tseng, L.; Hashkes, P. J.
Abstract : Background: Familial Mediterranean fever (FMF) is the most common hereditary autoinflammatory syndrome, affecting > 100, 000 people. FMF is caused by mutations in the MEFV gene, which encodes for the pyrin protein that is part of the inflammation complex that activates IL-1β. Evidence from case reports/series and one controlled study support IL-1 blockage as a potential treatment for FMF. Canakinumab (CAN) is a selective fully human monoclonal anti-IL-1β antibody approved in the EU and US for the treatment of cryopyrin associated periodic syndrome (CAPS). Objectives: This study served as a proof of concept to evaluate the role of CAN in the treatment of pediatric colchicine resistant (CR)-FMF. Methods: This was a 2-center open-label, single-arm study. The population consisted of CR FMF patients (pts) 4-20 years of age, with a history of at least 3 documented FMF attacks in the 3 months prior to enrollment. Pts entered a 30-day run-in period (RI) during which FMF attacks were documented in a diary. Pts who experienced an investigator-confirmed FMF attack during RI were eligible to enter the treatment phase and receive a SC injection of CAN 2 mg/kg (max 150 mg) every 4 weeks for three times with the 1 st dose given during an attack. The dose was doubled to 4 mg/kg (max 300 mg) if an attack occurred between Day 1 Baseline and Day 29 visits. Following the end of the treatment period, pts were followed until day 144 or until an attack occurred, whichever occurred first. Primary outcome was the proportion of pts with ≥50% reduction in FMF attack rate during the treatment vs. pretreatment period. Results: Fifteen Israeli pts (9 males, 6 females) entered the RI period and 7 (median age 9.5 yrs; 6.8-14.9 yrs) all with CR FMF advanced to the treatment period. In total, 6/7 (86%) pts had a ≥50% reduction in their FMF attack rate during the treatment period. The median attack rate prior to CAN was 2.7 per 28 days, this decreased to 0.3 per 28 days during treatment, representing a median 89% reduction. Five mild and 3 moderate attacks were experienced by 4 pts (1 with 4 attacks, 1 with 2 attacks and 2 with 1 attack) during the treatment period; 2 pts had their CAN dose uptitrated. Investigators rated FMF control as very poor (n=3), poor (n=3) or fair (n=1) at baseline; this improved to good (n=3) /very good (n=4) for all pts during the treatment period. Elevated median baseline CRP and SAA normalized by Day 8, ESR by Day 28 and all remained normal for remainder of trial. Only 5/7 pts experienced an attack during follow up; the median time to attack following the last CAN dose was 25 days (3-34 days). In all, 11 adverse events (AEs) in 4 pts were reported after the first CAN dose; all were mild except for 2 moderate AEs (Strep infection, laceration), none led to medication discontinuation. Conclusions: In this study of pediatric pts with colchicine resistant FMF, Canakinumab every 4 weeks substantially reduced the FMF attack rate consistent with that reported in adults. AEs were manageable. Further study is needed to better define the benefit of Canakinumab in FMF. Disclosure of Interest: R. Brik: None Declared, Y. Butbul Aviel: None Declared, S. Lubin Employee of: Novartis, E. Ben Dayan Employee of: Novartis, L. Tseng Employee of: Novartis, P. Hashkes Grant/research support from: Novartis, Consultant for: Novartis, Speakers bureau: Novartis